(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Description of the current state of occupational stress among nurses at Thai Binh Pediatric Hospital in 2025. Methods: This is a descriptive cross-sectional study using a population sampling method and the Expanded Nursing Stress Scale (ENSS). Results: The average stress score for nurses dealing with critically ill patients was 1.7 ± 0.48, with 12.6% of nurses feeling extremely stressed and helpless due to their inability to care for the patient. Over 90% of nurses experienced low to moderate stress levels related to colleague-related stress. The highest stress level was related to patients and their families, with 5.9% of nurses experiencing extreme stress when working with aggressive/violent patients/family members. Conclusion: Overall, nursing stress levels were mostly low to moderate, with 70.6% of nurses experiencing low stress, 29.4% experiencing moderate stress, and some specific clinical situations causing very high stress for a significant proportion of nurses.